2019
DOI: 10.1186/s40816-019-0131-1
|View full text |Cite
|
Sign up to set email alerts
|

Network pharmacology-based assessment to elucidate the molecular mechanism of anti-diabetic action of Tinospora cordifolia

Abstract: Background: Tinospora cordifolia is used traditionally for the treatment of diabetes and is used in various formulations. Scientific evidence is also available for its anti-diabetic potency under various animal models. However, the probable molecular mechanism of Tinospora cordifolia in the treatment of diabetes has not been illuminated yet. Hence, the present study dealt to elucidate the probable molecular mechanism of anti-diabetic effect of Tinospora cordifolia using network pharmacology approach. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
2

Relationship

3
7

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 42 publications
1
30
0
Order By: Relevance
“…Due to the complex composition of multiple phytoconstituents from all these medicinal plants, the mixture of this combination could modulate multiple proteins and would help to boost the immune system which can be explained via network pharmacology and gene-set enrichment analysis. Network pharmacology and gene set enrichment analysis are well-accepted approaches to identify the disease target, lead hit molecules and modulated pathways via "multiple component-protein interactions" [9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the complex composition of multiple phytoconstituents from all these medicinal plants, the mixture of this combination could modulate multiple proteins and would help to boost the immune system which can be explained via network pharmacology and gene-set enrichment analysis. Network pharmacology and gene set enrichment analysis are well-accepted approaches to identify the disease target, lead hit molecules and modulated pathways via "multiple component-protein interactions" [9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it has been demonstrated that how a single compound can modulate multiple proteins and regulate numerous pathways via the concept of gene-set enrichment analysis and network pharmacology approach [27][28][29][30]. The same principle can be applied via the "multi compound-multi protein" interaction in COVID-19 management.…”
Section: Discussionmentioning
confidence: 99%
“…Binding energy is evidence of the degree of positive interaction that occurs between a target molecule, such as an enzyme, and the test compound or ligand. It is also a measure of the compatibility between a compound and its intended target (Khanal et al 2019;Meduru et al 2016). Sitoindoside IX and most of the other phytocompounds present in the fruit extract exhibited an ideal pro le in the ADMET (Absorption, distribution, metabolism, excretion and toxicity) analysis, which indicates that the compound meets the ve requirements of the Lipinski rule which is a measure of the bioavailability of a molecule and its ability to pass through the blood brain barrier (Lin et al 2015;Patel et al 2017).…”
Section: Discussionmentioning
confidence: 99%